2012
DOI: 10.3390/polym4010747
|View full text |Cite
|
Sign up to set email alerts
|

Antibacterial Activity of Four Human Beta-Defensins: HBD-19, HBD-23, HBD-27, and HBD-29

Abstract: Human β-defensins (HBD) are a family of small antimicrobial peptides that play important roles in the innate and adaptive immune defenses against microbial infection. In this study, we predicted the mature sequences and assessed the antibacterial properties of synthetic HBD-19, HBD-23, HBD-27, and HBD-29 against three species of clinically relevant bacteria: Escherichia coli, Staphylococcus aureus and Pseudomonas aeruginosa. We also examined the cytotoxicity of each β-defensin to human cells. HBD-19 exhibited … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 10 publications
(3 citation statements)
references
References 33 publications
0
3
0
Order By: Relevance
“…Compared with α-defensins, β-defensins are produced by epithelial cells in a more ubiquitous fashion. Beta-defensins have been shown to be active against a range of Gram-positive and -negative enteric pathogens such as S. aureus , Streptococcus pyogenes , P. aeruginosa , E. coli , and Candida albicans ( Fusco et al., 2017 ) without causing significant toxicity to healthy host cells ( Chow et al., 2012 ). The gut microbiome also controls β-defensin secretion, although these AMP are still produced in the intestines of germ-free mice ( Putsep et al., 2000 ).…”
Section: Interactions Between Amp and The Gut Microbiomementioning
confidence: 99%
“…Compared with α-defensins, β-defensins are produced by epithelial cells in a more ubiquitous fashion. Beta-defensins have been shown to be active against a range of Gram-positive and -negative enteric pathogens such as S. aureus , Streptococcus pyogenes , P. aeruginosa , E. coli , and Candida albicans ( Fusco et al., 2017 ) without causing significant toxicity to healthy host cells ( Chow et al., 2012 ). The gut microbiome also controls β-defensin secretion, although these AMP are still produced in the intestines of germ-free mice ( Putsep et al., 2000 ).…”
Section: Interactions Between Amp and The Gut Microbiomementioning
confidence: 99%
“…hBD -19, 23, 27, and 29 are expressed in the male reproductive tract, where they protect spermatozoa from bacteria. Analysis of hBD-19, hBD-23, hBD-27, and hBD-29 against E. coli, S. aureus and P. aeruginosa, revealed that hBD-23 is the most effective in inhibiting the growth of these gram-negative and positive bacteria, with very low toxicity on normal human cells [39].…”
Section: B-defensinsmentioning
confidence: 99%
“…The number of b-defensins in a species has been shown to highly relevant to the ever-changing microbial challenges of the environment in which that species' inhabits (Tu et al 2015). It has been well-shown that different defensin alleles have different antimicrobial activities in vitro in a range of vertebrate hosts (Meredith et al 2008;Mukherjee et al 2009;Chow et al 2012). These studies suggest that the greater the variety of AMPs encoded, the greater the ability to combat a range of bacteria.…”
Section: Introductionmentioning
confidence: 99%